2018
DOI: 10.1523/jneurosci.2661-18.2018
|View full text |Cite
|
Sign up to set email alerts
|

Nociceptor Translational Profiling Reveals the Ragulator-Rag GTPase Complex as a Critical Generator of Neuropathic Pain

Abstract: Nociceptors, sensory neurons in the DRG that detect damaging or potentially damaging stimuli, are key drivers of neuropathic pain. Injury to these neurons causes activation of translation regulation signaling, including the mechanistic target of rapamycin complex 1 (mTORC1) and mitogen-activated protein kinase interacting kinase (MNK) eukaryotic initiation factor (eIF) 4E pathways. This is a mechanism driving changes in excitability of nociceptors that is critical for the generation of chronic pain states; how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
124
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
2

Relationship

5
3

Authors

Journals

citations
Cited by 111 publications
(143 citation statements)
references
References 78 publications
(45 reference statements)
6
124
0
Order By: Relevance
“…Activation of MNK-eIF4E signaling by type I IFNs has been observed in other cell types where it has been linked to increased immune surveillance (Joshi et al, 2009). Multiple previous studies have demonstrated that activation of MNK-eIF4E-mediated translation events are causative in the production of chronic pain states, including neuropathic pain (Moy et al, 2017; Megat et al, 2019; Shiers et al, 2019). Since both viral infections and prolonged production of type I IFNs can cause neuropathic pain, it is possible that type I IFN receptor signaling to MNK-eIF4E may be a key pathway for production of these types of neuropathies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Activation of MNK-eIF4E signaling by type I IFNs has been observed in other cell types where it has been linked to increased immune surveillance (Joshi et al, 2009). Multiple previous studies have demonstrated that activation of MNK-eIF4E-mediated translation events are causative in the production of chronic pain states, including neuropathic pain (Moy et al, 2017; Megat et al, 2019; Shiers et al, 2019). Since both viral infections and prolonged production of type I IFNs can cause neuropathic pain, it is possible that type I IFN receptor signaling to MNK-eIF4E may be a key pathway for production of these types of neuropathies.…”
Section: Discussionmentioning
confidence: 99%
“…A key pathway linking initial nociceptor activation to nociceptor hypersensitivity and potentially the development of chronic pain is engagement of translation regulation signaling (Obara and Hunt, 2014; Khoutorsky and Price, 2018; de la Pena et al, 2019). Importantly, eIF2α phosphorylation, mTORC1 activation and MNK-eIF4E signaling can all lead to persistent sensitization of nociceptors and all of these pathways have been linked to neuropathic pain disorders (Inceoglu et al, 2015; Khoutorsky et al, 2016; Moy et al, 2017; Megat et al, 2019; Shiers et al, 2019)…”
Section: Introductionmentioning
confidence: 99%
“…We have focused on using DRGs from uninjured mice and from human organ donors without a history of chronic pain. Many studies have demonstrated that cultured DRG neurons from mice with neuropathic pain retain some neuropathic qualities in vitro , in particular spontaneous activity in a sub-population of nociceptors [2; 33; 39; 63; 65]. This also occurs in human DRG neurons taken from people with neuropathic pain [39].…”
Section: Discussionmentioning
confidence: 99%
“…Some transcriptomic changes were found in mice but not conserved in humans. An example is caspase 6 ( Casp6 ) which has been implicated in many neuropathic pain models in mice [4; 5; 33]. This gene was over 3 fold increased in mouse DRG culture but unchanged in human DRG cultures.…”
Section: Discussionmentioning
confidence: 99%
“…The TRAP approach therefore represents a complimentary approach to bulk tissue and single cell sequencing capable to reveal novel insights into tissue diversity and pathological changes. In fact, two recent studies have employed the TRAP approach to primary nociceptors and uncovered unknown differences between trigeminal and dorsal root ganglia as well as unidentified driver genes for neuropathic pain [40,41].…”
Section: Single Cell Transcriptome Profiling Versus Cell Type Specifimentioning
confidence: 99%